A solid electrolyte membrane based on solvent structure, lithium battery and preparation method thereof
By introducing solvent structure and ether bonds into the solid electrolyte membrane and combining with the thermogenic phase separation process, the low conductivity and migration number of polymer solid electrolytes at room temperature is solved, and the efficient and stable circulation of lithium batteries is achieved.
Patent Information
- Application Number
- CN202311262708.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The existing polymer solid electrolytes have low ion conductivity and lithium ion migration number at room temperature, making it difficult to meet the practical application needs of solid lithium batteries.
A solid electrolyte membrane based on solvent structure is prepared by a dissolution-casting-volatilization process of thermally induced phase separation, including organic polymer A, polyethylene oxide B, lithium salt C and inorganic component D, and the migration and conductivity of lithium ions are improved by the solvent structure and ether bond conduction mechanism.
The real lithium ion conductivity at room temperature of solid electrolyte membrane is improved to 10-5S/cm level, enhancing the stable battery cycle performance of lithium batteries.
Smart Images

Figure CN117175002B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a solid electrolyte membrane based on a solvent structure, a lithium battery and a preparation method thereof. Background Art
[0002] With the rapid application and development of lithium-ion batteries, their safety and energy density issues have become increasingly prominent. The development of solid-state lithium batteries can achieve a dual improvement in safety and energy density. The solid electrolyte plays a dual role as a separator and electrolyte, playing a vital role in solid-state lithium batteries.
[0003] Among solid electrolytes, polymer solid electrolytes are favored due to their good processing performance, excellent interface characteristics, and compatibility with existing diaphragm preparation processes. Among them, polyethylene oxide (PEO) is widely used as the main body of polymer electrolytes because of its high dielectric constant and lithium ion conduction mechanism. This lithium ion conduction mechanism relies on the complexation of lithium ions dissociated from lithium salts with polymer segments, which mainly occurs in the amorphous region of the polymer. At room temperature, PEO has a high degree of crystallinity and insufficient dissociation of lithium salts. This type of polymer solid electrolyte exhibits a low ionic conductivity (no higher than 10 at 25°C). -6 S / cm) and lithium ion migration number (0.1-0.2, much lower than 0.2-0.3 of liquid lithium-ion batteries) make it difficult to put into practical application. Some technologies have been used to improve conductivity by adding plasticizers, but these plasticizers are usually liquid, and the prepared electrolyte membrane is not a pure solid electrolyte, so safety and energy density issues still exist.
[0004] Therefore, without adding small molecule plasticizer components, the ionic conductivity and lithium ion migration number of the polymer solid electrolyte are improved simultaneously, and the real lithium ion conductivity (the product of ionic conductivity and lithium ion migration number) at room temperature is increased to 10 -5 S / cm level is the top priority in solid electrolyte research. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a solid electrolyte membrane based on a solvent structure, a lithium battery and a preparation method thereof.
[0006] A solvent-structured solid electrolyte membrane is prepared by a solid electrolyte dissolution-casting-volatilization process based on thermally induced phase separation; the solid electrolyte comprises an organic polymer A, polyethylene oxide B and a lithium salt C; the organic polymer A is a short-branched polyethylene oxide with a functional structure, the functional structure of which comprises ether bonds located in the main chain and the side chains, and one or more solvent structures located in the side chains; the solvent structure is one or more of linear and cyclic carbonates and their derivatives, linear and cyclic carboxylates and their derivatives, and linear and cyclic ethers and their derivatives.
[0007] Preferably, the solid electrolyte further includes an inorganic component D, which is one or more of an oxide inorganic solid electrolyte, a sulfide inorganic solid electrolyte and an inorganic filler, with an average particle size of 20 nm to 2 μm, and an addition amount of the inorganic component D is 0 to 80% of the total weight of the solid electrolyte.
[0008] Preferably, the inorganic component D is one or both of the oxide inorganic solid electrolytes LATP and LLZO, with an average particle size of 200 nm, and the addition amount of the inorganic component D is 20% of the total weight of the solid electrolyte.
[0009] Preferably, the weight average molecular weight of the organic polymer A is 2000 to 2000000, and the ratio of the solvent structure segment is 1:20 to 1:1.
[0010] Preferably, the polyethylene oxide B has a linear structure and a weight average molecular weight of 100,000 to 4,000,000.
[0011] Preferably, the lithium salt C is one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate) and lithium difluorooxalatoborate.
[0012] A solid-state lithium battery comprises a positive electrode, a negative electrode and a solid electrolyte membrane, wherein the solid electrolyte membrane is between the positive and negative electrodes and is closely attached to the positive and negative electrodes.
[0013] A method for preparing a solid electrolyte membrane lithium battery based on a solvent structure comprises the following steps:
[0014] S1. Preparation of organic polymer A:
[0015] S1-1. Build a Schlenk line and replace the atmosphere in the container with nitrogen;
[0016] S1-2, weigh 100 parts by weight of n-hexane solvent, 0.1 to 1 parts by weight of copolymerization catalyst, and 1.5 to 23.5 parts by weight of ethylene oxide derivative containing solvent structure, and add them into a container;
[0017] S1-3, slowly drop 1.5 to 23.5 parts by weight of ethylene oxide into the container, stir slowly, and start the reaction;
[0018] S1-4, after the reaction time is reached, 100 parts by weight of methanol is added to terminate the polymerization reaction;
[0019] S1-5, filtering the reaction solution, taking the precipitate, first drying the precipitate at 40°C to 80°C at normal pressure for 8 to 36 hours, and then drying it at 20°C to 60°C at reduced pressure for 8 to 36 hours to obtain an organic polymer A;
[0020] S2. Preparation of solid electrolyte membrane:
[0021] S2-1, dissolving 5 to 15 parts by weight of an organic polymer A in 100 parts by weight of anhydrous acetonitrile as a solvent, and filtering to obtain a filtrate;
[0022] S2-2, add 5 to 15 parts by weight of polyethylene oxide B to the filtrate and fully dissolve it;
[0023] S2-3, continue to add lithium salt C to the solution and fully dissolve it so that the molar ratio of ethylene oxide units to lithium ions is 12 to 20;
[0024] S2-4, continue to add 0 to 16 parts of inorganic component D and stir evenly;
[0025] S2-5, pouring a proper amount of solution into a heated polytetrafluoroethylene resin mold, casting evenly, and drying at normal pressure at 40°C to 80°C to a solid state;
[0026] S2-6, drying the mold with the film at a reduced pressure of 20°C to 60°C for 24 hours, peeling off the film after the residual solvent is fully volatilized, and obtaining a solid electrolyte membrane;
[0027] S3. Assembling solid-state lithium batteries:
[0028] In an argon atmosphere, the positive electrode sheet, solid electrolyte membrane and lithium sheet are assembled into a solid-state lithium battery in the order of positive electrode, solid electrolyte membrane and negative electrode.
[0029] Preferably, the positive electrode uses 50 to 100 parts of active material lithium iron phosphate, 5 to 20 parts of conductive agent Super P, 5 to 20 parts of binder polyvinylidene fluoride, and 5 to 20 parts of binder succinonitrile, which are mixed in N-methylpyrrolidone to obtain a positive electrode slurry, coated on aluminum foil, and vacuum dried at 100 to 120° C. for 12 to 36 hours to obtain a positive electrode sheet.
[0030] Preferably, in step S2-5, the positive electrode plate is placed at the bottom of the polytetrafluoroethylene resin mold, or in step S3, the positive electrode and the solid electrolyte membrane are hot-pressed and bonded.
[0031] The beneficial effects of the present invention are:
[0032] The solid electrolyte membrane matrix provided by the present invention is a short-branched polyethylene oxide with copolymerized side chains containing both ether bonds and solvent structures. Since the short-branched polyethylene oxide of the present invention has a solvent structure, in addition to the two mechanisms of ether bond conduction mechanism and branched chain reduction of crystallinity of traditional short-branched polyethylene oxide, it can also provide a mechanism similar to the solvation structure of liquid lithium batteries, which simultaneously affects the dissociation of lithium salts and the rapid migration of lithium ions, and further improves the lithium ion migration number and ionic conductivity. The real lithium ion conductivity (the product of ionic conductivity and lithium ion migration number) of the corresponding solid electrolyte membrane at room temperature can be increased to 10 -5 S / cm level, achieving stable battery cycle of solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a graph showing the relationship between the number of solid-state battery cycle tests and the discharge specific capacity. DETAILED DESCRIPTION
[0034] The present invention will be further explained below in conjunction with specific embodiments.
[0035] Embodiment 1:
[0036] A solvent-structured solid electrolyte membrane is prepared by a solid electrolyte dissolution-casting-volatilization process based on thermally induced phase separation;
[0037] The solid electrolyte includes organic polymer A, polyethylene oxide B, lithium salt C and inorganic component D.
[0038] The organic polymer A is a short-branched polyethylene oxide containing a cyclic carbonate solvent structure with a weight average molecular weight of 50,000; the weight average molecular weight of polyethylene oxide B is 600,000; the lithium salt C is lithium bistrifluoromethylsulfonyl imide (LiTFSI); and the inorganic component D is a lithium lanthanum zirconium oxygen inorganic solid electrolyte (LLZO) with an average particle size of 200 nm.
[0039] A method for preparing a solid electrolyte membrane based on a solvent structure comprises the following steps:
[0040] S1: Preparation of organic polymer A
[0041] S1-1: Build a Schlenk line and replace the atmosphere in the container with nitrogen;
[0042] S1-2: Accurately weigh 100 parts (by weight, the same below) of n-hexane solvent, 0.2 parts of organotin phosphate catalyst, and 7.5 parts of propylene carbonate glycerol ether, an ethylene oxide derivative containing a solvent structure, and add them into a container;
[0043] S1-3: Slowly drop 17.5 parts of ethylene oxide into the container, stir slowly, and start the reaction;
[0044] S1-4: After the reaction time is reached, 100 parts of methanol are added to terminate the polymerization reaction;
[0045] S1-5: Filter the reaction solution and take out the precipitate. Dry the precipitate at 60°C under normal pressure for 24 hours and then at 40°C under reduced pressure for 24 hours to obtain an organic polymer A.
[0046] S2: Preparation of solid electrolyte membrane formed by polymer solid electrolyte SPE and composite solid electrolyte SCE
[0047] S2-1: dissolving 10 parts of organic polymer A in 100 parts of anhydrous acetonitrile as solvent, and filtering to obtain a filtrate;
[0048] S2-2: Add 10 parts of polyethylene oxide B to the filtrate and fully dissolve;
[0049] S2-3: Continue to add an appropriate amount of lithium salt C to the solution and fully dissolve it so that the molar ratio of ethylene oxide units to lithium ions (oxygen-to-lithium ratio) is 15;
[0050] S2-4: To prepare a solid electrolyte membrane formed by a composite solid electrolyte SCE, 4 parts of inorganic component D are added and stirred evenly;
[0051] S2-5: Pour an appropriate amount of solution into a heated polytetrafluoroethylene resin mold, cast evenly, and dry to a solid state at 60°C under normal pressure;
[0052] S2-6: The mold with the film is dried at 40° C. under reduced pressure for 24 hours, and the film is peeled off after the residual solvent is fully evaporated to obtain a solid electrolyte membrane.
[0053] S3: Assembling solid-state lithium batteries:
[0054] S3-1: The positive electrode uses 70 parts of active material lithium iron phosphate, 10 parts of conductive agent Super P, 10 parts of binder polyvinylidene fluoride, and 10 parts of binder succinonitrile, mixed in N-methylpyrrolidone (NMP) to obtain a positive electrode slurry, coated on aluminum foil, and vacuum dried at 110°C for 24 hours to obtain a positive electrode sheet;
[0055] S3-2: In order to achieve a better bonding effect between the positive electrode and the solid electrolyte membrane, in step S2-5, the positive electrode plate can be placed at the bottom of the polytetrafluoroethylene resin mold, or the positive electrode and the solid electrolyte membrane can be hot-pressed after step S3-1;
[0056] S3-3: In an argon atmosphere, assemble the positive electrode sheet, solid electrolyte membrane and lithium sheet into a solid-state lithium battery in the order of positive electrode, solid electrolyte membrane and negative electrode.
[0057] A solid-state lithium battery comprises a positive electrode, a negative electrode and a solid electrolyte membrane, wherein the solid electrolyte membrane is between the positive and negative electrodes and is closely attached to the positive and negative electrodes.
[0058] Embodiment 2:
[0059] The difference from Example 1 is that Example 2 adjusts the polymerization monomer ratio in S1, adding 12.5 parts of propylene carbonate glyceryl ether, an ethylene oxide derivative containing a solvent structure, and 12.5 parts of ethylene oxide. The remaining preparation steps are the same as those of Example 1.
[0060] Embodiment three:
[0061] The difference from Example 1 is that Example 3 adjusts the polymerization monomer ratio in S1, adding 17.5 parts of propylene carbonate glyceryl ether containing a solvent structure, an ethylene oxide derivative, and 7.5 parts of ethylene oxide. The remaining preparation steps are the same as those of Example 1.
[0062] Embodiment 4:
[0063] The difference from Example 1 is that Example 4 adjusts the ratio of the two organic polymers A and B in S2, adding 5 parts of organic polymer A and 15 parts of polyethylene oxide B. The remaining preparation steps are the same as those of Example 1.
[0064] Embodiment five:
[0065] The difference from Example 1 is that Example 5 adjusts the ratio of the two organic polymers A and B in S2, adding 15 parts of organic polymer A and 5 parts of polyethylene oxide B. The remaining preparation steps are the same as those of Example 1.
[0066] Embodiment six:
[0067] The difference from Example 1 is that in Example 6, the amount of lithium salt C added in S2 is adjusted, and the addition of lithium salt C makes the molar ratio of ethylene oxide units and lithium ions (oxygen-lithium ratio) be 12, and the remaining preparation steps are the same as in Example 1.
[0068] Embodiment seven:
[0069] The difference from Example 1 is that Example 7 adjusts the amount of lithium salt C added in S2. The addition of lithium salt C makes the molar ratio of ethylene oxide units to lithium ions (oxygen-to-lithium ratio) to be 18, and the remaining preparation steps are the same as Example 1.
[0070] Embodiment eight:
[0071] The difference from Example 1 is that in Example 8, no inorganic component D is added to S2. The remaining preparation steps are the same as those in Example 1.
[0072] Embodiment nine:
[0073] The difference from Example 1 is that in Example 9, the amount of the inorganic component D in S2 is adjusted to 8 parts. The remaining preparation steps are the same as those in Example 1.
[0074] Comparative Example 1:
[0075] The solid electrolyte includes polyethylene oxide B, lithium salt C and inorganic component D.
[0076] The weight average molecular weight of polyethylene oxide B is 600000; the lithium salt C is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI); and the inorganic component D is a lithium lanthanum zirconium oxygen inorganic solid electrolyte (LLZO) with an average particle size of 200 nm.
[0077] The lithium battery preparation method comprises the following steps:
[0078] S1: Preparation of solid electrolyte membrane formed by polymer solid electrolyte SPE and composite solid electrolyte SCE:
[0079] S1-1: 20 parts (by weight, the same below) of polyethylene oxide B are fully dissolved in 100 parts of anhydrous acetonitrile;
[0080] S1-2: Continue to add an appropriate amount of lithium salt C to the solution and fully dissolve it so that the molar ratio of ethylene oxide units to lithium ions (oxygen-to-lithium ratio) is 15;
[0081] S1-3: To prepare a solid electrolyte membrane formed by a composite solid electrolyte SCE, 4 parts of inorganic component D are added and stirred evenly;
[0082] S1-4: Pour an appropriate amount of solution into a heated polytetrafluoroethylene resin mold, cast evenly, and then dry to a solid state at 60°C under normal pressure;
[0083] S1-5: The mold with the film is dried at 40° C. under reduced pressure for 24 hours, and the film is peeled off after the residual solvent is fully evaporated to obtain a solid electrolyte membrane.
[0084] S2: Assembling solid-state lithium batteries:
[0085] S2-1: The positive electrode uses 70 parts of active material lithium iron phosphate, 10 parts of conductive agent Super P, 10 parts of binder polyvinylidene fluoride, and 10 parts of binder succinonitrile, mixed in N-methylpyrrolidone (NMP) to obtain a positive electrode slurry, coated on aluminum foil, and vacuum dried at 110°C for 24 hours to obtain a positive electrode sheet;
[0086] S2-2: In order to achieve a better bonding effect between the positive electrode and the solid electrolyte membrane, in step S2-5, the positive electrode plate can be placed on the bottom of the polytetrafluoroethylene resin mold, or the positive electrode and the solid electrolyte membrane can be hot-pressed after step S3-1;
[0087] S2-3: In an argon atmosphere, assemble the positive electrode sheet, solid electrolyte membrane and lithium sheet into a solid-state lithium battery in the order of positive electrode, solid electrolyte membrane and negative electrode.
[0088] Comparative Example 2:
[0089] The difference from Comparative Example 1 is that the amount of lithium salt C added in S1 is adjusted in Comparative Example 2, and an appropriate amount of lithium salt C is added so that the molar ratio of ethylene oxide units to lithium ions (oxygen-to-lithium ratio) is 12. The remaining preparation steps are the same as those of Comparative Example 1.
[0090] Comparative Example 3:
[0091] The difference from Comparative Example 1 is that the amount of lithium salt C added in S1 is adjusted in Comparative Example 3, and an appropriate amount of lithium salt C is added so that the molar ratio of ethylene oxide units to lithium ions (oxygen-to-lithium ratio) is 18. The remaining preparation steps are the same as those of Comparative Example 1.
[0092] Comparative Example 4:
[0093] The difference from Comparative Example 1 is that in Comparative Example 4, no inorganic component D is added to S1. The remaining preparation steps are the same as those of Comparative Example 1.
[0094] Comparative Example 5:
[0095] The difference from Comparative Example 1 is that the amount of the inorganic component D in S1 is adjusted in Comparative Example 5, and the amount of the inorganic component D is 8 parts. The remaining preparation steps are the same as those of Comparative Example 1.
[0096] The formulation differences between the embodiments and the comparative examples are shown in the following table, wherein the numerical ranges in brackets in the first row are the recommended dosage ranges of each component:
[0097]
[0098]
[0099] Determination of solid electrolyte film forming performance:
[0100] When preparing the solid electrolyte membrane formed by polymer solid electrolyte SPE and composite solid electrolyte SCE, the film-forming performance of the solid electrolyte can be qualitatively judged. Pour an appropriate amount of solution into a heated polytetrafluoroethylene resin mold. If it cannot be cast evenly, it means that the film-forming performance is very poor; if it can be cast evenly, but the film cannot be peeled off after the residual solvent is volatilized, it means that the film-forming performance is poor; if it can be cast evenly and the film can be peeled off after the residual solvent is volatilized, but the uniformity of the film is not good, it means that the film-forming performance is average; if it can be cast evenly and the film can be peeled off after the residual solvent is volatilized, the uniformity of the film is good, but the strength properties of the film are not good, it means that the film-forming performance is good; if it can be cast evenly and the film can be peeled off after the residual solvent is volatilized, the uniformity of the film is good, but the strength properties of the film are not good, it means that the film-forming performance is good; if it can be cast evenly and the film can be peeled off after the residual solvent is volatilized, the uniformity of the film is good, and the strength properties of the film are good, it means that the film-forming performance is excellent.
[0101] Solid electrolyte ion conductivity test:
[0102] A blocked cell composed of stainless steel sheet|solid electrolyte|stainless steel sheet was assembled, and EIS impedance spectrum was tested with a disturbance voltage of 5mV and a frequency test range of 0.1-1000kHz to obtain the bulk resistance of the solid electrolyte, and the ionic conductivity was calculated based on the size data of the solid electrolyte.
[0103] Solid electrolyte ion migration number test:
[0104] A non-blocking battery assembled with lithium sheet|solid electrolyte|lithium sheet was used, and the steady-state polarization method was used. A polarization voltage of 20mV was used for chronoamperometry and AC impedance testing. The migration contribution of lithium ions and other ions was determined by initial current, initial impedance, steady-state current, and steady-state impedance, and the ion migration number was calculated.
[0105] Solid-state battery cycle testing:
[0106] The assembled solid-state battery is ℃ Under the conditions of , charge and discharge experiments were carried out at a voltage of 2.5-3.8V and a rate of 0.1C to observe whether the battery can be stably cycled; for batteries with stable cycles, their first cycle discharge capacity, first cycle coulomb efficiency and capacity retention rate after 150 cycles were recorded.
[0107] Performance test results:
[0108]
[0109]
[0110] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A solid electrolyte membrane based on a solvent structure, characterized in that: It is made by the solid electrolyte through the dissolution-casting-evaporation process based on thermally induced phase separation; The solid electrolyte comprises an organic polymer A, polyethylene oxide B and a lithium salt C; The organic polymer A is a short-branched polyethylene oxide with a functional structure, wherein the functional structure includes ether bonds located in the main chain and the side chains, and one or more solvent structures located in the side chains; The organic polymer A is short-branched polyethylene oxide containing a cyclic carbonate solvent structure, and has a weight average molecular weight of 50,000; the weight average molecular weight of polyethylene oxide B is 600,000.
2. A solvent-structured solid electrolyte membrane according to claim 1, characterized in that: The solid electrolyte also includes an inorganic component D, which is one or more of an oxide inorganic solid electrolyte, a sulfide inorganic solid electrolyte and an inorganic filler, with an average particle size of 20 nm to 2 μm, and an addition amount of the inorganic component D is 0 to 80% of the total weight of the solid electrolyte.
3. A solvent-structured solid electrolyte membrane according to claim 2, characterized in that: The inorganic component D is one or two of the oxide inorganic solid electrolytes LATP and LLZO, with an average particle size of 200 nm, and the addition amount of the inorganic component D is 20% of the total weight of the solid electrolyte.
4. The solvent-structured solid electrolyte membrane according to claim 1, characterized in that: The lithium salt C is one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate) and lithium difluorooxalatoborate.
5. A solid-state lithium battery, characterized in that: It comprises a positive electrode, a negative electrode and a solid electrolyte membrane as claimed in claim 1 or 2, wherein the solid electrolyte membrane is between the positive and negative electrodes and is closely attached to the positive and negative electrodes.
6. A method for preparing a solid electrolyte membrane lithium battery based on a solvent structure, characterized in that: The following steps are involved: S1. Preparation of organic polymer A: S1-1. Build a Schlenk line and replace the atmosphere in the container with nitrogen; S1-2, weigh 100 parts by weight of n-hexane solvent, 0.2 parts of organotin phosphate catalyst, and 7.5 parts of propylene carbonate glycerol ether, an ethylene oxide derivative containing a solvent structure, and add them into a container; S1-3, slowly dropwise add 17.5 parts by weight of ethylene oxide into the container, stir slowly, and start the reaction; S1-4, after the reaction time is reached, 100 parts by weight of methanol is added to terminate the polymerization reaction; S1-5, filtering the reaction solution, taking the precipitate, first drying the precipitate at 60°C under normal pressure for 24 h, and then drying it at 40°C under reduced pressure for 24 h to obtain an organic polymer A; S2. Preparation of solid electrolyte membrane: S2-1, dissolving 5 to 15 parts by weight of an organic polymer A in 100 parts by weight of anhydrous acetonitrile as a solvent, and filtering to obtain a filtrate; S2-2, add 5 to 15 parts by weight of the polyethylene oxide B as claimed in claim 1 to the filtrate and fully dissolve it; S2-3, continue to add the lithium salt C as claimed in claim 1 to the solution and fully dissolve it so that the molar ratio of ethylene oxide units to lithium ions is 12 to 20; S2-4, continue to add 0 to 16 parts of the inorganic component D as described in claim 2 or 3, and stir evenly; S2-5, pouring an appropriate amount of solution into a heated polytetrafluoroethylene resin mold, casting evenly, and drying at normal pressure at 40°C to 80°C to a solid state; S2-6, drying the mold with the film at 20°C to 60°C under reduced pressure for 24 h, peeling off the film after the residual solvent is fully volatilized, and obtaining a solid electrolyte membrane; S3, assembling solid-state lithium battery: In an argon atmosphere, the positive electrode sheet, solid electrolyte membrane and lithium sheet are assembled into a solid-state lithium battery in the order of positive electrode, solid electrolyte membrane and negative electrode.
7. The method for preparing a solid electrolyte membrane lithium battery based on a solvent structure according to claim 6, characterized in that: The positive electrode uses 50 to 100 parts of active material lithium iron phosphate, 5 to 20 parts of conductive agent Super P, 5 to 20 parts of binder polyvinylidene fluoride, and 5 to 20 parts of binder succinonitrile, which are mixed in N-methylpyrrolidone to obtain a positive electrode slurry, coated on aluminum foil, and vacuum dried at 100 to 120°C for 12 to 36 hours to obtain a positive electrode sheet.
8. The method for preparing a solid electrolyte membrane lithium battery based on a solvent structure according to claim 7, characterized in that: In step S2-5, the positive electrode plate is placed at the bottom of the polytetrafluoroethylene resin mold, or the positive electrode and the solid electrolyte membrane are hot-pressed and bonded in step S3.
Citation Information
Patent Citations
Composite solid polymer electrolyte membrane and preparation method and application thereof
CN111540948A
Positive plate as well as preparation method and application thereof
CN114784223A